Extracellular Vesicles: Schistosomal Long-Range Precise Weapon to Manipulate the Immune Response - Avni, Dror; Avni, Orly (Frontiers in Cellular and Infection Microbiology, 2021)
Schistosomiasis (Bilharziasis), a neglected tropical disease that affects more than 240 million people around the world, is caused by infection with the helminth parasite Schistosoma. As part of their secretome arsenal, schistosomes release extracellular vesicles (EVs) that modulate the host immune response; Schistosomes utilize EV-harbored miRNAs to upregulate the innate immune response of the M1 pathway and downregulate the differentiation toward the adaptive Th2 immunity. Also, an egg-derived miRNA increases the percentage of regulatory T cells. Altogether the schistosomal immunoediting generates a parasitic friendly environment, but it should be applied carefully as restrained Th2 response is crucial for the host survival and successful excretion of the schistosomal eggs. Evidence indicates a selective targeting of the schistosomal EVs, however, the underlying mechanisms are unclear yet. The schistosomal strategy is in accordance with the hygiene hypothesis, attributing the dramatic increase in recent decades in allergy and other diseases associated with an imbalanced immune response to the reduced exposure to infectious agents that co-evolved with humans during evolution. Deciphering the bioactive cargo, function, and selective targeting of the parasite-secreted EVs may facilitate the development of novel tools for diagnostics and delivered therapy to schistosomiasis, as well as to immune-associated disorders.